2012
DOI: 10.1039/c2jm31187a
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of triptycene-based microporous poly(benzimidazole) networks

Abstract: We demonstrate the synthesis of two triptycene-based microporous poly(benzimidazole) networks through condensation of triptycene-hexone with dialdehyde in refluxing glacial acetic acid containing ammonium acetate. The benzimidazole-linkage in the resulting polymers is confirmed by Fourier transform infrared and solid-state 13 C CP/MAS NMR spectroscopy. The spindle-shaped morphology of the obtained polymers was also observed through scanning electron microscopy. The materials, with Brunauer-Emmet-Teller (BET) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
79
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(84 citation statements)
references
References 43 publications
5
79
0
Order By: Relevance
“…[6][7][8][14][15][16] These results, in conjunction with another recent study, 6 highlight that 1 is an attractive and synthetically accessible precursor towards that end. Our current work aims to use 1 as a component in more robust metal-organic assemblies and frameworks, with potential to combine porosity and redox-active properties.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…[6][7][8][14][15][16] These results, in conjunction with another recent study, 6 highlight that 1 is an attractive and synthetically accessible precursor towards that end. Our current work aims to use 1 as a component in more robust metal-organic assemblies and frameworks, with potential to combine porosity and redox-active properties.…”
Section: Discussionsupporting
confidence: 68%
“…[13][14][15] Diaminosubstituted phenylene residues in triptycenes are readily converted by Schiff base condensations into extended arenes, 16 annelated heterocycles 11,12 or polydentate metalbinding domains. [8][9][10] Alternatively, catechol functions in triptycene derivatives have been used as components in hydrogen-bonded supramolecular assemblies, or incorporated into larger crown ether receptors [1][2][3][4][5] or microporous polymer materials.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, it is not easy to control the bubbling of oxygen into the reaction system, which is necessary for the formation of imidazole ring. With these consideration in mind, Zhao et al [89] reported the synthesis of microporous poly(benzimidazole) networks through condensation reaction between dione, dialdehyde, and ammonium acetate. This approach is a template-free and catalyst-free condensation and produces no by-products.…”
Section: Covalent Organic Frameworkmentioning
confidence: 98%